2008
DOI: 10.1002/pssc.200779232
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanowires: chemical growth, electrodeposition, and application to intracellular nano‐sensors

Abstract: In this paper we present our results on growth, characterization, and nano‐devices based on ZnO nano‐structures. The ZnO nano‐structures were grown by mainly two methods, the catalytic Vapor Liquid Solid (VLS) and the low temperature chemical growth. We show that by multiple coating combined with low temperature chemical growth, well aligned with size controlled ZnO nanowires on silicon substrates can be achieved. The dissolution, due to its important on the stability of ZnO nano‐structures in aqueous medium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…The major challenges for process engineers are to reproducibly grow aligned, high aspect ratio, n-type ZnO nanostructures, control their resistivity and measure the nature (electrons or holes) of charge carriers within the structures. Non-aligned n-type ZnO nanostructures can be grown by appropriate doping in conjunction with the techniques such as high temperature vapor phase methods, RF Magnetron sputtering, MOCVD, pulsed-laser ablation, microwave, hydrothermal and sol-gel [6][7][8][9][10][11][12]. Electrochemical deposition is another simple technique which has been explored to grow ZnO nanowire structures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The major challenges for process engineers are to reproducibly grow aligned, high aspect ratio, n-type ZnO nanostructures, control their resistivity and measure the nature (electrons or holes) of charge carriers within the structures. Non-aligned n-type ZnO nanostructures can be grown by appropriate doping in conjunction with the techniques such as high temperature vapor phase methods, RF Magnetron sputtering, MOCVD, pulsed-laser ablation, microwave, hydrothermal and sol-gel [6][7][8][9][10][11][12]. Electrochemical deposition is another simple technique which has been explored to grow ZnO nanowire structures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In this frame the different features observed in our samples can be understood and explained; at low R VI/II values, the mobility of Zn adatoms is high, and the diffusion length is sufficient enough to allow the surface energies govern the growth process. For ZnO, the surface energy of the c-plane -(0001)-is greater than those of m-and a-planes, (10 À10) and ( [11][12][13][14][15][16][17][18][19][20], respectively [30,31], so the growth of c-oriented nanorods with m-plane facets tends to minimize the total surface energy. This energetic anisotropy of the surfaces can also influence the reactivity, the binding and the incorporation of the incoming precursors.…”
Section: Effect Of Vi/ii Ratio R Vi/iimentioning
confidence: 99%
“…Several methods have been established to synthesize ZnO nanorod arrays such as physical vapor transport [7][8][9], chemical vapor deposition [10,11], electrodeposition [12,13], pulsed laser deposition [14,15] and metal organic chemical vapor deposition (MOCVD) [ [16][17][18]. The latter technique, further to the scalable advantages due to its industrial character, has been demonstrated to be well adapted to the synthesis of ZnO nanowires and nanorods arrays with well controllable shape, good quality and reproducibility [19].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NRs/NWs are extensively applied in various sensing applications fields, e.g. biosensors [44][45][46][47][48][49][50][51], biomarker [52][53], drug delivery [54][55] , chemical sensors [56][57][58], gas sensors [59][60], pH sensors [61], humidity sensor [62][63][64], UV sensors [65][66][67][68][69], temperature sensors [70][71], and pressure/force/mass/load sensors [72][73][74][75]. Also, the high performances of several types of sensors have been enhanced by utilizing different metals doped ZnO nanorods, e.g.…”
Section: Sensing Applications Based On Zno and Tm-doped Zno Nanostrucmentioning
confidence: 99%